Island lakes in Poland and their legal protection - Choiński, Adam; Macias, Andrzej; Skowron, Rajmund (Quaestiones Geographicae, 2025)
The purpose of this study is to pioneer the inventory lake islands using topographic maps and orthophotomaps. Additionally, for the first time, an attempt was made to determine what percentage of lake islands in Poland are covered under the legal system of nature protection. A significant percentage of islands under legal protection indicates their enormous importance for geobiodiversity. An analysis of topographic maps edited around 1975 showed a total of 1115 islands, including 541 in the Masurian Lake District, 410 in the Pomeranian Lake District and 164 in the Greater Poland and Kuyavian Lake Districts. They are located on 556 lakes. The total area of all the islands is 2395.8 ha. The highest number of islands is on Mamry (35 islands). The largest island is Ostrów (99.5 ha) on Jeziorak. Whereas the analysis of orthophotomaps from 2010 to 2011 showed that there are also 1115 islands on 550 lakes, with a total area of 2161.57 ha. Differences in the results obtained between data from topographic maps and orthophotomaps may result, for example, from the damming of lake surfaces, from the transformation of islands into peninsulas, from the merger or division of islands, etc. According to the orthophotomaps, the largest island is Wielimska (94.6 ha) on Wielimie. Mamry has the largest number of islands (32). Out of the 1115 islands identified on topographic maps, 963 (86.4%) are legally protected, covering a total area of almost 2309 ha. Surprisingly, this accounts for as much as 96.4% of the area of all islands.